ANALISIS BIBLIOMETRIK PENELITIAN BURUNG MALEO - Daud Yusuf; Dewi Wahyuni K Baderan; Marini Susanti Hamidun; Sukirman Rahim; Iswan Dunggio (Jurnal Bionatural, 2024)
This study examines the development of research trends on maleo bird natural habitat conservation. The study aims to find out: The development of the number of Sinta indexed national and google scholar indexed international publications on maleo birds. Data collection was conducted using four keywords, namely Maleo Bird Conservation, Maleo Bird, Maleo Bird and Maleo Bird Conservation in the span of 2019 - 2024. Data was analysed using Publish of Perish and VosViewer. The results showed 299 articles published in 2019-2024. There were 47 articles (15.72%) published in 2019, 45 articles (15.05%) in 2020, 50 articles (16.72%) in 2021, 76 articles (25, 42%) in 2022, 71 articles (23.75%) in 2023 and until March 2024 there were only 10 articles (3, 34%) that discussed maleo birds. Based on the mapping of research linkages on maleo, the results are 4 clusters, each cluster 1 with 4 keywords. Cluster 2 with 4 keywords, cluster 3 with 2 keywords and finally cluster 4 also with 2 keywords